Evaluation of the antibacterial effect of Epigallocatechin gallate on the major pathogens of canine periodontal disease and therapeutic effects on periodontal disease mice - Song, Peijia; Hao, Yibing; Lin, Degui; Jin, Yipeng; Lin, Jiahao (Frontiers in Microbiology, 2024)
Background Periodontal disease (PD) is a prevalent oral affliction in canines, with limited therapeutic options available. The potential transmission of oral bacteria from canines to humans through inter-species contact poses a risk of zoonotic infection. Epigallocatechin gallate (EGCG), the principal catechin in green tea polyphenols, exhibits antibacterial properties effective against human PD. Given the clinical parallels between canine and human PD, this study explores the feasibility of employing EGCG as a therapeutic agent for canine PD. Methods and results Initially, a survey and statistical analysis of bacterial infection data related to canine PD in China were conducted. Subsequently, the primary pathogenic bacteria of canine PD were isolated and cultivated, and the in vitro antibacterial efficacy of EGCG was assessed. Furthermore, verify the therapeutic effect of EGCG on a mouse PD model in vivo. The high-throughput 16S rRNA gene sequencing identified Porphyromonas, Fusobacterium, Treponema, Moraxella, and Capnocytophaga as the genera that distinguishing PD from healthy canines’ gingival crevicular fluid (GCF) samples in China. The anaerobic culture and drug susceptibility testing isolated a total of 92 clinical strains, representing 22 species, from 72 canine GCF samples, including Porphyromonas gulae, Prevotella intermedia, Porphyromonas macacae, etc. The minimum inhibitory concentration (MIC) ranging of EGCG was from 0.019 to 1.25 mg/mL. Following a 7 days oral mucosal administration of medium-dose EGCG (0.625 mg/mL), the abundance of periodontal microorganisms in PD mice significantly decreased. This intervention ameliorated alveolar bone loss, reducing the average cementoenamel junction to the alveolar bone crest (CEJ-ABC) distance from 0.306 mm ± 0.050 mm to 0.161 mm ± 0.026 mm. Additionally, EGCG (0.3125 mg/mL) markedly down-regulated the expression of inflammatory factor IL-6 in the serum of PD mice. Conclusion Our research demonstrates the significant antibacterial effects of EGCG against the prevalent bacterium P. gulae in canine PD. Moreover, EGCG exhibits anti-inflammatory properties and proves effective in addressing bone loss in a PD mouse model. These findings collectively suggest the therapeutic potential of EGCG in the treatment of canine PD. The outcomes of this study contribute valuable data, laying the foundation for further exploration and screening of alternative antibiotic drugs to advance the management of canine PD.